THE CHARACTERISTICS OF TOP MANAGMENT AND FIRM’S EARNINGS MANAGEMENT: THE EVIDENCE FORM THAILAND - Rojana Khunkaew; Yang Qingxiang (Copernican Journal of Finance & Accounting, 2019)
This study investigates the association between Top Management Team (TMT) characteristics and Earnings Management (EM) by examining 1,855 observations of Thai-firm listed in period of 2013–2017. This study employs Modified Jones model (1991) and Roychowdhury (2006) to measure accruals and real activities earnings management, respectively. The findings in this paper reveal TMT characteristics influence on both in AEM and REM and firms with older, long tenure and possessing CPA certification of TMT lead to decrease in AEM level. In contrast, TMT tenure has positive influence to REM level that implies long tenure of TMT tends to manage earnings through operation activities instead of discretionary accruals. However, the percentage of female members and master’s degree education of TMT have no significant association with earnings management.